Curriculum and Civic Education Teaching in Indonesia - Komara, Endang (EDUCARE, 2017)
ABSTRACT: The curriculum is a set of plans and arrangements concerning objectives, content and instructional materials, and ways used as guidelines for the implementation of learning activities to achieve certain educational goals. The purpose of Indonesian national education is to develop the potential of learners to become human beings, who believe and fear to Allah as One God, have a noble character, healthy, knowledgeable, capable, creative, independent, and become a democratic and responsible citizen. Indonesia has incorporated Civic Education programs in the school curriculum about a decade after the proclamation of independence in August 1945. This article, by using the qualitative method and descriptive approach, tries to explore the curriculum and Civic Education teaching in Indonesia. The findings show that more than half a century of educational education, even at all levels of education from elementary, secondary to higher education, still leaves the general and classical issues of low levels of political literate, moreover to achieve the goal of creating intelligent and skilled Indonesian citizens. Political literacy is not only political knowledge, but the ability of citizens who qualified both in aspects of knowledge, skills, and values and attitudes. In learning of Civic Education, teachers are required to develop an interesting learning process, fun, challenging, and forming learners to be able to think critically and constructively. Civics teachers should be able to present contextual learning materials, relate subject matter with real conditions in the field, set theory with practice, between expectations and reality, identify problems, and encourage learners to come up with alternative problem solving.KEY WORDS: Curriculum Development; Teaching-Learning Process; Social Life; Citizenship Education; Teachers of Civics Education.About the Author: Prof. Dr. Haji Endang Komara is a Full Professor in Sociology of Education and as Head of STKIP (College of Education and Teacher Training) Pasundan in Cimahi, West Java, Indonesia. For academic interests, the author is able to be contacted via his e-mail address at: endang_komara@yahoo.co.idÂ How to cite this article? Komara, Endang. (2017). âCurriculum and Civic Education Teaching in Indonesiaâ in EDUCARE: International Journal for Educational Studies, Volume 10(1), August, pp.23-32. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877. Chronicle of the article: Accepted (May 20, 2017); Revised (July 3, 2017); and Published (August 30, 2017).